Preparing Sponge Dough for Making Bread Using Wheat Flour Cultured in 5% Saline - Naganori Ohisa; Kazuto Endo; Toshikazu Komoda (Fermentation)
A 5% salt solution was used to make sponge dough from wheat flour. We devised a new starter (wheat flour saline culture) by adding 5% saline to wheat flour and incubating it for 24 h. The dough’s rise was enhanced by adding wheat flour saline culture to the dough: after two hours, the dough volume increased by 20–30% compared to the control. Furthermore, the specific volume of the bread increased from 2.25 cm3/g in the control to 2.73–3.47 cm3/g when sugar or other auxiliary ingredients were not added to it. Wheat flour saline culture contained a large number of halotolerant bacteria. The addition of wheat flour saline culture increased the air bubble size and specific volume of the bread.